Creep rupture behaviour of modified 9Cr-1Mo heat-resistant steel strengthened with different mechanisms. (2nd November 2019) - Zhu, Lin; Liu, Xinbao; Fan, Ping; Dan, Yong; Wang, Litao
ABSTRACT: The creep rupture behaviours and microstructural changes of a modified 9Cr-1Mo heat-resistant steel were investigated at 853 K. Analysis of creep results suggests that dislocation climb is the dominant deformation mechanism with true stress exponent of 5 under the present conditions. Based on the microstructural analysis, strengthening contributions from M23 C6 carbides and MX carbonitrides were clarified. The M23 C6 carbides can promote grain boundary strengthening by exerting Zener pinning forces, whereas MX carbonitrides can enhance the creep strength by interacting with mobile dislocations to induce threshold stress. Besides, softening of the steel is related not only to the decrease of dislocations, but also the coarsening of precipitates and substructures. The value of creep damage tolerance factor is close to 6.6, which further confirms that the creep damage is mainly attributed to the microstructural degradations, such as the coarsening of precipitates and substructures and decrease of dislocations.